The effectiveness of community service program in developing social competence and personality competence for Islamic teacher training students - Dina Khusniah (ATTARBIYAH: Journal of Islamic Culture and Education, 2018)
Community Service Program (KKN) is a miniature of social reality for students to play a role in society. The program is expected to develop social competence and personality competence, especially as candidate teacher of PAI (Islamic education). This research is conducted on PAI UIN Walisongo Semarang students who follow KKN activity in academic year 2016/2017.  Data collection is done by interview, observation, anddocumentation. The results of the study explained that social competence during the Community Service Program (KKN) as a whole shows the development. On the personal competence of PAI students during theCommunity Service Program (KKN) shows most of the progress. This is evidenced by the suitability of field data with indicators of personality competence, including (1) Steady and stable personality; (2) Adultpersonality; (3) Wise personality; (4) Authoritative Personality; and (5) Personality that reflects noble character. Based on the findings of researchers, there are student who have not shown progress on these fourindicators. As for factors that affect the development of students’ personalities PAI, including internal factors in the form of motivation in the activities of the Community Service Program (KKN), and externalfactors such as environment.